2018
DOI: 10.1038/s41598-018-32323-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Depletion of BRD8 Causes p53-Dependent Apoptosis and Induces a DNA Damage Response in Non-Stressed Cells

Abstract: Regulation of the chromatin state is crucial for biological processes such as the regulation of transcription, DNA replication, and DNA damage repair. Here we show that knockdown of the BRD8 bromodomain protein - a subunit of the p400/Tip60 complex - leads to p21 induction, and concomitant cell cycle arrest in G1/S. We further demonstrate that the p53 transcriptional pathway is activated in BRD8-depleted cells, and this accounts for upregulation of not only p21 but also of pro-apoptotic genes, leading to subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…It has now been confirmed that when DNA damage occurs in G1 cells, the G1/S checkpoint can be triggered via at least two signaling pathways, the ATM/p53/p21 and the ATM/CHK2/CDC25C pathways 216 . For instance, post irradiation, ATM is activated, and ATM phosphorylates p53 and MDM2, promoting dissociation of p53 from MDM2 and inhibiting p53 translocation from the nucleus to cytoplasm; on the other hand, CHK2 is activated, which phosphorylates and stabilizes p53, and the increased level of p53 triggers the transcription of downstream genes such as p21, contributing to G1/S arrest [217][218][219] . Compared to the ATM/p53/p21 pathway, the ATM/CHK2/CDC25C pathway induces rapid signaling in response to DNA damage 220 .…”
Section: Activation Of Cell Cycle Checkpointsmentioning
confidence: 99%
“…It has now been confirmed that when DNA damage occurs in G1 cells, the G1/S checkpoint can be triggered via at least two signaling pathways, the ATM/p53/p21 and the ATM/CHK2/CDC25C pathways 216 . For instance, post irradiation, ATM is activated, and ATM phosphorylates p53 and MDM2, promoting dissociation of p53 from MDM2 and inhibiting p53 translocation from the nucleus to cytoplasm; on the other hand, CHK2 is activated, which phosphorylates and stabilizes p53, and the increased level of p53 triggers the transcription of downstream genes such as p21, contributing to G1/S arrest [217][218][219] . Compared to the ATM/p53/p21 pathway, the ATM/CHK2/CDC25C pathway induces rapid signaling in response to DNA damage 220 .…”
Section: Activation Of Cell Cycle Checkpointsmentioning
confidence: 99%
“…In the immune-risk model, bromodomain containing 8 (BRD8) was an androgen receptor coactivator, while TNF receptor associated factor 3 (TRAF3) was also involved in functioning of a variety of receptors. e knowledge of BRD8 in immune regulation was rare; however, it was related to p53-dependent apoptosis and could be a chemosensitizing target in colorectal cancer [41][42][43]. TRAF3 has been found to interplay with toll like receptors and TNF receptors in lymphocytes, and previous studies have found TRAF3 could attenuate noncanonical NF-kB pathway, influencing B cell and T cell development and recruitment through chemokine regulation [44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…[26][27] The probes resulting from this work provide new opportunities for the study of the role of BRD8's bromodomain within the NuA4 complex, as well as ligands for affinity enrichment and targeted degradation approaches. In this regard, an accumulating body of work has implicated a tumor-supportive role for BRD8 in colorectal carcinoma, 17,[19][20] and more recently in hepatocellular carcinoma, 21 characterized by its frequent overexpression, correlation with poor prognosis, and contribution to traditional chemotherapy resistance. 20 These studies link this biology to BRD8's influence in DNA repair pathways and associated signaling, consistent with the longstanding appreciation of a role for NuA4 and the TIP60 acetyltransferase activity in these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…20 These studies link this biology to BRD8's influence in DNA repair pathways and associated signaling, consistent with the longstanding appreciation of a role for NuA4 and the TIP60 acetyltransferase activity in these pathways. 18,28 The tools developed herein will enable assessment of bromodomain inhibitors' ability to recapitulate antiproliferative effects of genetic knockdown of BRD8 in these contexts, 17,[20][21] or if further adaptation as targeted protein degradation probes will be required. Finally, the findings of this study further highlight the power of chemoproteomics workflows to provide both unbiased interrogation of target space and comparative assessment of complex engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation